EFEKTIVITAS PEMANFAATAN MEDIA PEMBELAJARAN AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR SISWA - A. Roni (UNISAN JURNAL, 2024)
The purpose of this study is to describe the use of Audio Visual Media in improving student learning outcomes and student learning outcomes after using audio visual media in Islamic religious education subjects for class VI at Madrasah Aliyah Muhammadiyah Kota Jambi. This research includes descriptive qualitative research, data collection carried out by several methods namely, observation, interviews and documentation. as for the steps taken are data reduction, data display (data presentation), verification (drawing conclusions). From the data collected, the writer analyzes it by means of inductive thinking that departs from specific conclusions and then becomes a conclusion. The results of the study found that the use of Audio Visual learning media in improving Islamic Religious Education learning outcomes for grade VI was said to be effective because PAI teachers could use Audio Visual Media correctly and well and could produce good learning outcomes. Audio Visual Media For teachers can facilitate the transformation of knowledge while for students it can be useful as motivation to learn.